2020
DOI: 10.3233/jad-191312
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk for Alzheimer’s Disease Moderates the Association Between Medial Temporal Lobe Volume and Episodic Memory Performance Among Older Adults

Abstract: Background: A complex set of interactions between biological, genetic, and environmental factors likely underlies the development of Alzheimer's disease (AD). Identifying which of these factors is most associated with AD is important for early diagnosis and treatment. Objective: We sought to examine genetic risk and structural brain volume on episodic memory in a sample of older adults ranging from cognitively normal to those diagnosed with AD. Methods: 686 adults (55-91 years old) completed a 3T MRI scan, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
3
1
0
Order By: Relevance
“…Whereas our moderation analysis results are consistent with those previously found for PHS ( Prieto et al, 2020 ), our meditational analyses reported novel findings. Mediation models in cognitive neurogenetic research provide a useful framework for directional hypotheses, which are generally appropriate for cognitive neurogenetics because effects generally transmit from genes to brain and cognition, rather than vice versa.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Whereas our moderation analysis results are consistent with those previously found for PHS ( Prieto et al, 2020 ), our meditational analyses reported novel findings. Mediation models in cognitive neurogenetic research provide a useful framework for directional hypotheses, which are generally appropriate for cognitive neurogenetics because effects generally transmit from genes to brain and cognition, rather than vice versa.…”
Section: Discussionsupporting
confidence: 92%
“…The predictive capabilities of PHS may have contributed to our finding of genetics moderating the relationship between the right fimbria/hippocampus VR and episodic memory. Similar findings were observed in a prior study in old adults ( Prieto et al, 2020 ) that the PHS moderated episodic memory through the left hippocampus in the MCI group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations